High-voltage nanosecond pulse generator for magnetron gun triggering - Reshetnyak, N.G.; Romas’ko, V.P.; Chertishchev, I.A. (Вопросы атомной науки и техники, 2018)
A small-sized nanosecond generator was developed to trigger a magnetron gun. A voltage pulse of amplitude up to 20 kV is applied to anode for gun triggering. Rise and fall fronts of high-voltage pulse are 20 and 70 ns consequently. Thyratron TGI1-500/16 with a low-inductive storage capacitance was used as a switch. The capacitance is discharged to the cable transformer (input wave impedance 25 Ohm, transformation ratio n = 2) operating at a load of 500 Ohm (the capacitance of the magnetron gun anode to ground is 40 pF). Using this resistance transformer on RF cables makes it possible to change rapidly the polarity of the trigger pulse. Розроблено малогабаритний наносекундний генератор для запуску магнетронної гармати. Імпульс напруги амплітудою до 20 кВ для запуску гармати подається на її анод. Фронти наростання і спаду високовольтного імпульсу становлять 20 і 70 нс. В якості комутатора використано тиратрон ТГІ1-500/16 з малоіндуктивною накопичувальною ємністю. Розряд ємності здійснюється на кабельний трансформатор (вхідний хвильовий опір 25 Ом, коефіцієнт трансформації n = 2), що працює на навантаження 500 Ом (ємність анода магнетронної гармати на землю 40 пФ). Використання даного трансформатора опорів на радіочастотних кабелях дає можливість оперативно змінювати полярність запускаючого імпульсу. Разработан малогабаритный наносекундный генератор для запуска магнетронной пушки. Импульс напряжения амплитудой до 20 кВ для запуска пушки подаётся на её анод. Фронты нарастания и спада высоковольтного импульса составляют 20 и 70 нс. В качестве коммутатора использован тиратрон ТГИ1-500/16 с малоиндуктивной накопительной ёмкостью. Разряд ёмкости осуществляется на кабельный трансформатор (входное волновое сопротивление 25 Ом, коэффициент трансформации n=2), работающий на нагрузку 500 Ом (ёмкость анода магнетронной пушки на землю 40 пФ). Использование данного трансформатора сопротивлений на радиочастотных кабелях дает возможность оперативно изменять полярность запускающего импульса.